An Early Bronze Age burnt mound trough and boat fragment with accompanying palaeobotanical and pollen analysis at Nant Farm, Porth Neigwl, Llŷn Peninsula, Gwynedd. (1st December 2017) - Smith, George; Caseldine, Astrid; Griffiths, Catherine; Peck, Inga; Nayling, Nigel; Jenkins, David
This paper describes the excavation of a multi-phase complex of burnt mound activity, dated to the first half of the second millennium cal BC, sealed by later water-laid sediments and a buried soil. A well-preserved timber plank-built trough and associated stakes retained some details of woodworking techniques and incorporated at least one piece of a 'sewn-plank' Bronze Age boat. The various deposits provided palaeoenvironmental evidence about the activity associated with the trough and its environment as well as a pollen record of the later environmental changes including those that may have led to its abandonment.